Navigating The Nexus of Technology and Character Development in Education: A Qualitative Comparative Analysis - Nugraha, Firman; Muaripin, Muaripin; Ayundhari, Vidia Lantari; Prawira, Yudha Andana (FASTABIQ: JURNAL STUDI ISLAM, 2025)
This article examines the intricate relationship between technology and character development in education, focusing on the Indonesian context while drawing comparisons with Sweden. It explores the challenges and opportunities that arise as technology becomes increasingly integrated into educational settings. Employing a qualitative comparative analysis, this study investigates how technological advancements influence educational transformation and its interconnectedness with industrial demands. The findings reveal that while technology has a transformative impact on education, its integration into character development presents unique cultural and value-based challenges. Countries like Indonesia, where traditional, religious, and ethical values play a significant role in shaping education, face different obstacles compared to Sweden, which adopts a highly digitalized and secular approach. Through comparative analysis, the study highlights these contrasting strategies, emphasizing the need for a balanced approach that leverages technology while safeguarding cultural identity and moral education. Furthermore, the role of educators is crucial in this transition, requiring them to adapt to digital transformations while fostering students' holistic character development. This research underscores the need for strategic policies and pedagogical frameworks that harmonize technological advancements with the preservation of ethical and cultural values. By offering insights into how different nations navigate these challenges, the study contributes to the broader discourse on global educational trends in the digital era.Keywords: Educational technology; Character Development; Cultural and Ethical Values